2019
DOI: 10.3389/fgene.2019.00540
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Polymorphisms in Circadian Clock and Lipid Metabolism Genes With 2nd Trimester Lipid Levels and Preterm Birth

Abstract: Deregulation of the circadian system in humans and animals can lead to various adverse reproductive outcomes due to genetic mutations and environmental factors. In addition to the clock, lipid metabolism may also play an important role in influencing reproductive outcomes. Despite the importance of the circadian clock and lipid metabolism in regulating birth timing few studies have examined the relationship between circadian genetics with lipid levels during pregnancy and their relationship with preterm birth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Some studies have reported the association of hPER3 with obesity, for instance, PER3 methylation levels are related to childhood obesity 42 , hPER3 increased the BMI of those who sleep too late 13 , rs228669 of hPER3 showed association with triglycerides 43 , and cg10059324 also showed correlation with insulin resistance 44 . In our experiment, PER3 in humans or mice showed high expression in adipose tissues than in other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported the association of hPER3 with obesity, for instance, PER3 methylation levels are related to childhood obesity 42 , hPER3 increased the BMI of those who sleep too late 13 , rs228669 of hPER3 showed association with triglycerides 43 , and cg10059324 also showed correlation with insulin resistance 44 . In our experiment, PER3 in humans or mice showed high expression in adipose tissues than in other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, there were no statistically significant differences in exercise and sleep conditions of pregnant women between the control and case groups, however, we still found they tended to spend more time on TV and phones and less time doing exercise on the whole. As exercise and sleep conditions could influence blood lipid levels, this phenomenon should arouse our attention [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…AREG encodes amphiregulin, a ligand of epidermal growth factor receptors (EGFRs), which are expressed in human uterine tissues at labour [73] and EGFR signalling was identified as relevant to human parturition by previous integrative analysis [21]. PER3 is a circadian rhythm gene, which encodes a transcriptional repressor that controls the circadian clock system in peripheral tissues [74] and, incidentally, a genetic polymorphism within its 'rs228669' coding region [74] has been linked to high risk spontaneous preterm births [75].…”
Section: Plos Onementioning
confidence: 99%